Sediment - ostracode relationship in the gulf of Mannar, off Toticorin, east coast of India - Hussain, S. M.; Manivannan, V.; Ragothaman, V. (Journal of Nepal Geological Society, 1997)
An attempt has been made to establish the sediment-ostracode relationship, in the gulf of Mannar, off Tuticorin, south east coast of India. 48 sediment samples were collected from 12 sampling stations. Twelve bottom sediment samples were collected once in three months, for a period of one year, so as to represent the four seasons (winter, summer, southwest Monsoon and northeast Monsoon). Calcium carbonate and organic matter content of each sample were correlated against the ostracode population recovered in the respective sample. An increase in the CaCO3 percentage and a decrease in the organic matter content generally favor a higher population size.